2021
DOI: 10.1080/23311886.2021.1947560
|View full text |Cite
|
Sign up to set email alerts
|

Technology transfer for social benefit: Ten principles to guide the process

Abstract: The transfer of knowledge and inventions from universities to society has a twofold objective: the business community should be advanced by innovations, and society should benefit. Economic success is relatively easy to measure (e.g., increased sales), but social benefits are not. Thus, we presented a matrix of 10 principles for the assessment of the social value of technologies. With this understanding, technology transfer processes can be designed to lead to products and services that are more valuable in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on the results, the authors concluded that: "the knowledge generated by universities makes an important contribution to economic growth through technology transfers, which makes firms more innovative" (García-Vega 2021). However, the benefits of knowledge transfer and innovation from academia need to be seen in a broader context: they have not only a business-economic dimension but also a social dimension as they should serve to solve society's problems and meet its needs (Madl & Radebner, 2021).…”
Section: U Ni Ver Si T Ies' Responsi Ble Resea Rch An D I Nnovat Ion ...mentioning
confidence: 99%
“…Based on the results, the authors concluded that: "the knowledge generated by universities makes an important contribution to economic growth through technology transfers, which makes firms more innovative" (García-Vega 2021). However, the benefits of knowledge transfer and innovation from academia need to be seen in a broader context: they have not only a business-economic dimension but also a social dimension as they should serve to solve society's problems and meet its needs (Madl & Radebner, 2021).…”
Section: U Ni Ver Si T Ies' Responsi Ble Resea Rch An D I Nnovat Ion ...mentioning
confidence: 99%
“…Studies conducted by Stanton and Young [7] have shown that individuals of various age groups have reduced stress levels and increased trust in the system while adopting Adaptive Cruise Control (ACC). Madl and Radebner [8] delineated four possible benefits associated with contemporary technology. Initially, there exists the possibility that individuals may not effectively use it, so nullifying any advancements in safety.…”
Section: Overall Efficiency Of Use Of Novel In-vehicle Advancementmentioning
confidence: 99%